Influence of wood ash pre-treatment on leaching behaviour, liming and fertilising potential. (January 2019) - Maresca, A.; Krüger, O.; Herzel, H.; Adam, C.; Kalbe, U.; Astrup, T.F.
Highlights: Changes in the ANC curve occurred within the first two weeks of hardening. Phosphorous release in neutral ammonium citrate was observed in the range of 30–51%. Loose and granulated ashes demonstrated similar leaching behaviour in column tests. Granules could withstand one month of continuous leaching preserving their shape. Abstract: In Denmark, increasing amounts of woody biomass are being used for the production of renewable energy, resulting in more wood ashes being generated. While these materials have been mainly landfilled, wood ashes may also be utilised for fertilizing and liming purposes on top of soils. Pre-treatments involving hardening or granulation may be carried out prior to soil application. In this study, two Danish wood ash samples were hardened and/or granulated. Lab-hardening induced rapid changes in the shape of the acid neutralisation capacity curve of the ashes. Up-flow column tests, assuming local equilibrium conditions, were employed to investigate the leaching from pre-treated ashes. Granules and loose ashes demonstrated similar leaching behaviours, indicating that similar geochemical processes were governing their leaching. In comparison with untreated fresh ashes, the hardened ashes demonstrated reduced leaching of Ca, Ba, Pb and Zn with concentration levels generally below or close to the analytical limits of quantification; to the contrary, the leaching of As, P, Sb, Si, V and Mg was enhanced in the hardened ashes. The release of alkalinity was reduced by hardening. In general, all granules were barely breakable by finger-pinching and they could withstand one month of continuous leaching, preserving their overall shape. The solubility of phosphorous in neutral ammonium citrate indicated that about 30–51% of the total P content in the ash samples was released, suggesting that the ashes could be potentially valuable as P-fertiliser if applied onto soil.